Rancang Bangun Anti Rust Electric Control pada Mesin CNC - Muhammad Ziaâ€™ulhaq Iqramullah; Fipka Bisono; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The use of a machine with Computer Numerical Control (CNC) technology is one of thealternatives in a manufacturing process. In the process of machining using Computer NumericalControlled (CNC), it is necessary to check the condition of the machine, because in machiningprocess requires good machine quality, tools using, cooling components, material in use andappropriate feeding procedure, so it can produce desired product. The common obstacles in CNCmachine is to overcome the corrosion that usually occurs in telescopic cover in CNC machine, so onthe method of forced flow (ICCP) with microcontroller system is applied. This method was chosenbecause it is easy to control the protection current that given to the system, this research using anodethat made from graphite material and cathode which is stainlees steel 304, with temperature variable40â„ƒ and giving protection current 0,25 mA and 0,50 mA corresponds to the protection surface areaof 27.7172 cm2which requires a 0.066 mA current. Corrosion testing using the weight loss method ismeasuring the corrosion rate by measuring weight loss. From the previous test result usingimmersion test for 2 days corrosion rate that happened at 6,2008 mm / year then with rust electriccontrol test for 2 days resulted corrosion rate 2,5293 mm / year at current 0,25 mA whereas 0, 50 mAproduced a corrosion rate of 1.8580 mm / year. It can be concluded that the increase in the currentinput can slow down the rate of corrosion that occurs in SS 304 material.